2016
DOI: 10.1177/0954411916667410
|View full text |Cite
|
Sign up to set email alerts
|

PEEK-OPTIMA as an alternative to cobalt chrome in the femoral component of total knee replacement: A preliminary study

Abstract: PEEK-OPTIMA™ (Invibio Ltd, UK) has been considered as an alternative joint arthroplasty bearing material due to its favourable mechanical properties and the biocompatibility of its wear debris. In this study, the potential to use injection moulded PEEK-OPTIMA™ as an alternative to cobalt chrome in the femoral component of a total knee replacement was investigated in terms of its wear performance. Experimental wear simulation of three cobalt chrome and three PEEK-OPTIMA™ femoral components articulating against … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
46
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 50 publications
(48 citation statements)
references
References 36 publications
2
46
0
Order By: Relevance
“…The roughness of the PEEK surface and the counterface, as well as temperature, sliding speed, and contact pressure should be considered in a tribiological study (4). The wear rate could not be measured in this study due to the limited experimental conditions; however, recent studies have proved a relatively good wear property of "PEEK-on-PE" frictional pairs (2,15).…”
Section: Thoughts and Progressmentioning
confidence: 95%
See 1 more Smart Citation
“…The roughness of the PEEK surface and the counterface, as well as temperature, sliding speed, and contact pressure should be considered in a tribiological study (4). The wear rate could not be measured in this study due to the limited experimental conditions; however, recent studies have proved a relatively good wear property of "PEEK-on-PE" frictional pairs (2,15).…”
Section: Thoughts and Progressmentioning
confidence: 95%
“…Interest has been raised in the development of all‐polymer prosthetic knee joints , which can be wear‐resistant, reducing stress shielding and metal ions in the bone. Meanwhile, a preliminary study by Cowie et al reported that with respect to wear rate of PE tibial components against cobalt chrome or PEEK implants, PEEK is promising as an alternative bearing material to a cobalt chrome alloy in the femoral component. Thus, the “PEEK‐on‐PE” bearings are suggested to be advantageous in knee joint components and have a high potential for the next generation of knee replacements.…”
mentioning
confidence: 99%
“…2,3 In addition, meeting the strict surface quality requirements in the manufacturing process and the time-consuming process of polishing the surface of Co-Cr-Mo alloy femoral component are challenging. 4 However, there has been growing interest in polyether-etherketone (PEEK) material as an arthroplasty-bearing material, such as PEEK-on-PEEK articulations in the spine 5,6 as well as total knee implants, 3,7 and it is regarded as an alternative to Co-Cr-Mo alloy in knee arthroplasty. PEEK is a thermoplastic polymer known to be resistant to fatigue strain.…”
Section: Introductionmentioning
confidence: 99%
“…9 Therefore, wear resistance in vivo and generation of wear particles are the issues of greatest concern for joint prosthesis. Previous studies had proved PEEK material resists fatigue strain and wear in vitro well, 7,10,11 but there has been few in vivo study as yet of PEEK-on-highly cross-linked polyethylene (HXLPE) TKA implants to investigate the wear behavior under the complicated mechanical and chemical environment of knee joints.…”
Section: Introductionmentioning
confidence: 99%
“…With a Young's modulus (~4 GPa) closer to that of cortical bone (~18 GPa) than metal titanium 59 alloy (110 GPa) 11 or CoCr (220 -230 GPa) 12 , the concept of an all-polymer TKR with PEEK 60 replacing the metal femoral component has been explored with initial wear tests showing 61 promising results 13 . Theoretically all-polymer knee replacements should reduce stress 62 shielding on the host bone after TKR, offering an attractive alternative to current TKR designs 63 in addition to reduced machining manufacturing costs 14,15 .…”
Section: Introduction 32mentioning
confidence: 99%